CERTIFICATION OF PERSONNEL AS A FACTOR OF DEVELOPMENT OF MOTIVATION OF THE SUBJECT OF WORK - T. Gorobets; O. Dorogina (Вестник университета, 2017)
The article discusses an important issue - the activities of the organization to conduct certification activities. In the basis of preparation of certification of employees of the organization is the diagnostic approach - definition of motivation to work. It is determined that the identification of motivation is the most informative approach, which promotes increase of efficiency of professional activity, creation of intentions for professional development.